PERKEMBANGAN KEBIJAKAN DAERAH SEBAGAI PARADIGMA DASAR UNTUK PENENTUAN KEBIJAKAN MENGELOLA POTENSI KEBERAGAMAN - Fadlan, Fadlan (Soumatera Law Review, 2019)
The implementation of the regional autonomy principle must be able to put forward the principle of decentralization, this core essence becomes very important because there is a clear relationship and governance between the central government and the regional government so that on the basis of initiatives, creativity and operands to be achieved in carrying out power efforts to realize a just and prosperous society as stated in the opening of the 1945 Constitution of the Republic of Indonesia, and the most important in the context of developing and advancing regions for regional interests based on people's aspirations.